Application of Edible Coating Water Soluble Based Chitosan Nanoparticles and Polyvinyl Alcohol in Strawberry (Fragaria Ananassa) Storage - Likia Salsa Billa; Yunita Rachmawati; Titis Kusumaninghayu; Pandu Lintang Nugroho; Angela Merici Pusparani; Esa Ghanim Fadhallah; Diki Danar Tri Winanti; Madi Hartono (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2025)
Strawberries (Fragaria ananassa) are highly sought after for their vibrant color and unique flavor. However, their high perishability and rapid quality degradation lead to significant post-harvest losses and a decrease in market value. This study aimed to evaluate the effect of an edible coating based on WSC nanoparticles and PVA on the quality characteristics of strawberries during storage. The research methodology included the synthesis of WSC nanoparticles, preparation of the coating solution, application to strawberries, and subsequent storage. A Completely Randomized Design (CRD) with a single-factor arrangement was utilized, comprising five PVA concentrations (0%, 2%, 3%, 4%, and 5%) with three replications. The results demonstrated that the application of the nanoparticle WSC-PVA-based edible coating effectively reduced weight loss and delayed physical deterioration. Increasing PVA concentrations led to a more effective preservation of total soluble solids (°Brix), a lower weight loss percentage, and a slower decline in vitamin C content. Higher PVA concentrations were found to reduce the rate of quality degradation and moisture loss. The coating formulation containing 4% PVA (P3) exhibited the best performance, maintaining a water content of 92.24%, total soluble solids of 2 °Brix, a pH of 4.3, a weight loss of 30%, and a vitamin C retention rate of 9.02%. The findings of this study offer a valuable solution for farmers to mitigate strawberry quality decline and provide new insights for future research on food preservation.